2019
DOI: 10.1109/access.2019.2945545
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Artificial Neural Network Applications to Pattern Recognition

Abstract: The era of artificial neural network (ANN) began with a simplified application in many fields and remarkable success in pattern recognition (PR) even in manufacturing industries. Although significant progress achieved and surveyed in addressing ANN application to PR challenges, nevertheless, some problems are yet to be resolved like whimsical orientation (the unknown path that cannot be accurately calculated due to its directional position). Other problem includes; object classification, location, scaling, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
205
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 445 publications
(211 citation statements)
references
References 167 publications
(131 reference statements)
1
205
0
5
Order By: Relevance
“…Pattern recognition processes has three main tasks: data pre-processing, data representation and decision making. A simple feed-forward neural network can be trained for pattern recognition tasks such as image processing and biometric identification [13]. ANNs can be described as non-linear machine learning methods.…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…Pattern recognition processes has three main tasks: data pre-processing, data representation and decision making. A simple feed-forward neural network can be trained for pattern recognition tasks such as image processing and biometric identification [13]. ANNs can be described as non-linear machine learning methods.…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…However, the generalization capabilities of ANN-based models [32] cannot be assured. More generic and stable approaches are therefore required to solve these problems.…”
Section: Related Workmentioning
confidence: 99%
“…This method gave a highly robust and accurate result, but it did not focus on textual information. Abiodun et al 28 did a comprehensive review of PR, which showed ANN was the best comparable method using in statistical, fuzzy, structural techniques to address the PR problems. Abiodun et al 29 did a survey based on the ANN contribution, which accuracy, latency, volume, processing speed, performance, fault tolerance, and scalability was high.…”
Section: Literature Surveymentioning
confidence: 99%